The Impact of Aid on Growth an aid disaggregation approach - Bazoumana Ouattara; Eric Strobl (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
This paper investigates the impact of aid on growth. A clear departure from the vast majority of the existing literature is that we a disaggregate aid by functional classification. Using the GMM SYS approach to dynamic panel estimator we test the three main competing specifications in the aid and growth literature for a sample of aid recipient countries over the 1974-2001 period. Our results clearly show that the different categories of aid exert different effects on growth. Indeed, we find that project aid exerts a positive and significant impact on growth whilst financial programme aid generally impacts on growth negatively. Our results also show that the impact of non-financial aid, technical assistance grants and food aid, is statistically insignificant. We found, however, no evidence to suggest that policy enhances the growth effect of the aid categories. Our non-linearity tests suggest that only project aid is associated with diminishing returns. Finally, our results confirm the finding that climate related conditions affect the working of aid (project).
Keywords: C2; F3; 330; Aid; Growth; Dynamic Panel Methods